The Early Development of the American Cotton Manufacture - Day, Clive (Quarterly Journal of Economics, 1925)
Chronological table by states of the foundation of cotton factories. Comparison with contemporary statistics, 453. — Accuracy of the dates, 456. — Omission of defunct factories from the table, 458. — Chronological table by states of textile companies incorporated, 460. — Inferences from the tables. Importance of the period of the war of 1812, 463. — Relation of factory establishments to tariff legislation, 468.